THE ROLE OF NURSES IN LIFE - Turayeva Shohista Ravshanovna (Лучшие интеллектуальные исследования, 2024)
Abstract: Good nurses show concern for patients by caring for them effectively and attentively to foster their well-being. However, nurses cannot be taught didactically to be “good” or any trait that characterizes a good nurse. Nurses’ self-awareness of their role traits warrants further study.